Implementasi Sistem Pervasive Pada Smart Home Berbasis Bluetooth Versi 4.0 Menggunakan Modul BLE HM-10 dan Sensor - I Wayan Boby Astagina Naghi; Sabriansyah Rizqika Akbar; Barlian Henryranu Prasetio (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Smart Home with pervasive concept can find Bluetooth device and the services. Smart home constructed can control many node so energy saving is required. Thus, appropriate Bluetooth for this pervasive Smart Home is Bluetooth 4.0 (BLE). Bluetooth 4.0 is derivated from Classic Bluetooth technology which low-cost, long-life battery caused by minimum energy consumption, and easy development. Author implements the pervasive smart home system with smartphone as the controller through BLE communication. Smart Home consists of lamp node (Arduino Nano, LED, and modul BLE HM-10), temperature and humidity node (Arduino Nano, sensor DHT11, and modul BLE HM-10), and fan node (Arduino Uno, kipas DC, dan modul BLE HM-10). Android application as the controller constructed using MIT App Inventor 2. Scanning done by application then continued by choosing BLE HM-10 node and connect them through CONNECT button. When connection formed, SERVICES button pushed to knowing the services given by BLE HM-10 node. If the service has been displayed on smartphone, user can input number instruction to operating the BLE HM-10 node. Feedback of operation result will be displayed on the smartphone. DISCONNECT button pushed to disconnect the connection. BLE HM-10 performance also tested in case of signal quality and energy consumption comparison with Bluetooth HC-05. Based on the test result, caused of pervasive concept, when scanning process, application can recognize BLE HM-10 node and the services displayed when requested by user. Feedback and service displayed in the form of sentence with maximum amount of 20 characters because maximum payload size of BLE HM-10 is 20 byte, and the sentence more than 20 characters will be displayed one by one. BLE HM-10 has maximum signal quality of 98% and minimum quality of 20% and better in term of energy saving (5,69 mW) than Bluetooth HC-05 (13,56 mW)